Composição fotojornalística e história: função testemunhal como ato performativo e interação de linguagens - Casadei, Eliza Bachega [UNESP] (2014)
Assuming that testimony in photojournalism must be understood as a historical and performative act, the aim of this article is to discuss how the testimonial function of journalistic photography was constantly re-signified in Brazilian news magazines during the twentieth century. This redefinition has a relation with the different ways in which testimonial function was hinged to news report (in its broadest elements) and how this imperative appeared on its discursive form in writing narrative. As trustee of a narrative intended to be realistic, photojournalism articulates, from techniques and codes of narration, a series of referential and informational strategies. These strategies, however, have changed over time, based on different modes of narration by image and its accreditation in reality.